Modern problems of perfection of elite light athletic sportsmen’s technical skillfulness perfection - Kolot, A.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: perfection of elite sportsmen’s technical skillfulness in competition kinds of light athletic. Material: the data of more than 60 literature sources were systemized. Expert questioning of 36 coaches, having experience of work with elite sportsmen, was carried out; documents of training process planning were analyzed as well as sportsmen’s diaries (n=244). Results: we have presented main principles of sportsmen’s technical skillfulness perfection and elucidated characteristics of technical training methodic. We have determined main priorities of technical training building for light athletes at every stage of many years’ perfection. Dynamic of competition practice volume has been found as well as main requirements to selection of training means of technical orientation. The data of bio-mechanical criteria of sportsmen’s technical skillfulness assessment have been supplemented. Conclusions: effectiveness of sportsmen’s training methodic is determined by realization of previous stages’ technical potential in final competition results. It can be achieved by determination of means of and methods of different orientation rational correlation.